AN ANALYSIS OF LANGUAGE STYLES USED IN ‟TO ALL THE BOYS I‟VE LOVED BEFORE” MOVIE - Intan Sakinah Normalita; Pininta Veronika Silalahi (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This thesis is entitled An Analysis of Language Style Used in ‟Too All The Boys I’ve Loved Before‟ Movie. The objective of study is to describe language style using movie data through an informal style which can be categorized into slang style and colloquial style, to find out the most frequently used language style in the movie. The research design is a qualitative descriptive based on Mandell and Kirszner's theory about the types informal in the form of slang, and colloquial styles and data source are the types of data taken from the dialogue. Language is one part of human life when interacting and taking our everyday activities with other people. The language style is the variety of language used to communicate between individuals, situation and context affect the use of language style when communicating. The researcher focus on slang style and colloquial style that i found in a movie script. The author is Jenny Han, and the published is Susan Johnson. This data was published on Netflix in August 2018 in season 1 and season 2 in 2020. Then, season 3 was released in 2021. This study found that there are 22 slang style and 39 colloquial style and the characters used in the movie different language styles in different situations.